2015
DOI: 10.1111/iej.12467
|View full text |Cite
|
Sign up to set email alerts
|

Chemical removal of necrotic periodontal ligament on delayed replanted teeth by sodium hypochlorite: morphological analysis and microhardness indentation test of cementum

Abstract: Use of either 1% NaOCl for 15 min or 5.25% NaOCl for 5 min was effective at removing necrotic PDL from the delayed replanted teeth whilst having a minimal influence on cementum integrity. However, 1% NaOCl for 15 min was less damaging to cementum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…O en la resorción radicular inflamatoria (RRI), las raíces pueden parecer más cortas de lo que normalmente se espera y / o tener extremos de raíces irregulares, y tendrán radiolucencias apicales adyacentes al ápice radicular, aparecerá como muescas en forma de cráter en la superficie radicular radiopaca. 29,30 En cuanto a la realización de la endodoncia extrabucalmente Giannetti et al establecieron que el tratamiento de la avulsión dental; en un paciente con un tiempo extraoral mayor a una hora y con ápice maduro, será la terapia de endodoncia extraoral inmediata, ya que parece ser el método ideal para la eliminación de cualquier estímulo agitador.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O en la resorción radicular inflamatoria (RRI), las raíces pueden parecer más cortas de lo que normalmente se espera y / o tener extremos de raíces irregulares, y tendrán radiolucencias apicales adyacentes al ápice radicular, aparecerá como muescas en forma de cráter en la superficie radicular radiopaca. 29,30 En cuanto a la realización de la endodoncia extrabucalmente Giannetti et al establecieron que el tratamiento de la avulsión dental; en un paciente con un tiempo extraoral mayor a una hora y con ápice maduro, será la terapia de endodoncia extraoral inmediata, ya que parece ser el método ideal para la eliminación de cualquier estímulo agitador.…”
Section: Discussionunclassified
“…Sin embargo, el 1% de NaOCl durante 15 minutos fue menos perjudicial para el cemento. 30 En Venezuela este manejo de la raíz es mucho más factible de realizar debido a que el Endogain no es fácil de adquirir. En el presente reporte de caso solo se lavó la raíz con hipoclorito al 5,25% y el alveolo con solución fisiológica antes de la reimplantación muy probablemente a esto se deba la reabsorción inflamatoria ya que no se eliminó completamente el tejido necrótico del ligamento periodontal.…”
Section: Discussionunclassified
“…NaClO is the most commonly used endodontic irrigation solution due to its tissue‐dissolving activity and bactericidal effects 21‐23 . Some studies showed that the use of NaClO solution effectively removed necrotic PDL and was more effective at protecting the cementum layer than mechanical removal by scraping the root surface 24 . In the present experiment, the pulp tissues were extirpated with an endodontic file, and the pulp debris and the periodontal ligaments were removed by being soaked in 1.5% NaClO for 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 1 upper and 2 lower impacted wisdom teeth discarded as medical wastes were used as human TRC samples. The TRC surface was exposed by removing the remaining PDLs using sodium hypochlorite treatment, as described previously . Complete removal of PDLs without damage to the TRC surface was confirmed using optical microscopy of decalcified histological sections of separate sample pieces.…”
Section: Methodsmentioning
confidence: 99%